Analisis Pengaruh Partisipasi Orang Tua dalam Kegiatan Sekolah Terhadap Prestasi Siswa - Mendrofa, Erlin Talenta; Tafonao, Riska Sri Handayani; Zega, Ika Lestari; Harefa, Noveri Amal Jaya (Indo-MathEdu Intellectuals Journal, 2024)
One of the responsibilities of parents as first adults is to educate children about their family environment, as children are usually around their mother and father when they are born. This research uses a qualitative approach. This study aims to analyze the influence of parental participation in school activities on student achievement. This research is qualitative research with a descriptive approach. The subjects used in this study are parents and students. The determination of the subject uses purposive techniques. The data collection technique used is interviews with parents and students. The data analysis used is qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The results of this study show that parental participation in school involves physical presence, learning support, collaboration with teachers, and involvement in important decisions for children's development. Parents' participation in school activities has a significant positive impact. Their involvement strengthens the school-family relationship, providing benefits for children's development in academic, social, and emotional aspects